EFEKTIVITAS PEMBELAJARAN PENDIDIKAN JASMANI DI SMA NEGERI SURABAYA TENTANG PEMANFAATAN SARANA DAN PRASARANA DALAM KEGIATAN EKSTRAKURIKULER TAHUN PELAJARAN 2012/2013 - TAUFIK, MUHAMMAD (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract In teaching physical education and health exercise, to acquire the necessary learning effectiveness of adequate infrastructure. Adequate facilities and infrastructure are still not met by any existing school. It is found in schools that are in the city to reduce the learning physical education and health exercise land for the benefit of outside learning physical education and health exercise. For the researcher interested in conducting research on the assessment of facilities and infrastructure in schools. This assessment is done by conducting survey research using the research instrument adopted from Base Data Physical Education and Sport Indonesia (PDPJOI). Of instruments PDPJOI researchers only took about facilities and infrastructure assessment. The research was conducted at SMAN 2 Surabaya and Surabaya SMAN 4 as the study sample. From the research results can be generally concluded that the utilization of facilities and infrastructure will assist teachers in improving learning effectiveness physical education and health exercise in school. Of the results if the instrument, the value obtained physical education and health exercise infrastructures existing in SMAN2 Surabaya by 120 in the category of being. While the value of the facilities and infrastructure of existing physical education and health exercise in Surabaya SMAN 4 of 100 in the category of being. Keywords: facilities and infrastructure, the effectiveness of learning.